DIGITAL TRANSFORMATION OF CUSTOMS POLICY IN THE CONTEXT OF GLOBALIZATION: INTERNATIONAL EXPERIENCE AND MODERNIZATION DIRECTIONS FOR UKRAINE - BONDARENKO, Natalya; SHYSHOV, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the digital transformation of customs policy in the context of globalization, taking into account international experience and identifying the priority directions for modernizing Ukraine’s customs system. It is substantiated that, under current conditions, customs duties have lost their purely fiscal nature and have transformed into a multifunctional instrument for regulating foreign economic activity, ensuring economic security, and supporting integration into the global economic space. The study demonstrates that key determinants of effective customs administration include the level of digitalization of procedures, the development of risk-oriented control, and the quality of the institutional environment. The experience of the European Union, the United States, Singapore, China, and Mexico is analyzed regarding the combination of tariff regulation with digital tools of customs administration. It is established that the introduction of electronic single-window systems, the integration of interagency information resources, and the use of analytical platforms significantly reduce customs clearance time, lower transaction costs, and enhance procedural transparency. Special attention is devoted to the role of the WTO Trade Facilitation Agreement and the institution of the Authorized Economic Operator in forming a partnership-based model of interaction between the state and business. It is substantiated that the development of the AEO contributes to balancing security and the speed of goods movement, reducing administrative burdens, and strengthening trust in customs authorities. The main problems of Ukraine’s customs system are identified, including fragmented information systems, insufficient automation of procedures, and limited application of risk-oriented approaches. Based on these findings, the article justifies the priority directions for the modernization of Ukraine’s customs system, the implementation of which will facilitate the development of a transparent, efficient, and institutionally capable customs service aligned with the customs environment of the European Union.